The Effects of Liquidity, Solvency, and Profitability on Stock Price (a Study in PT. Telekomunikasi Indonesia Tbk. Period of 2004-2018) - Kusnandar Kusnandar; Maya Sari (DINASTI RESEARCH, 2020)
This study aims to determine the effect of liquidity, solvency and profitability on stock prices. The research was conducted at PT Telekomunikasi Indonesia Tbk during the period of 2004 - 2018. Through a multiple regression analysis, the effect of liquidity, solvency and profitability was investigated by measuring current ratio, debt to equity ratio, and return on assets effects on stock prices. The findings reveal that changes in liquidity, profitability, and solvency are able to explain the changes being occurred on the share price of PT Telkom Indonesia during the period. Out of the three determinants, profitability performance is the only determinant that has a significant impact on stock price. These findings indicate that profitability performance becomes one factor that is most considered by investors in making investment decisions. Further, the profitability performance is also able to provide positive signals to the investors regarding the company prospects in the future.